Pro Windows Phone 7 Development - Cameron, Rob (Apress : Imprint: Apress, 2011)
The Windows Phone 7 platform provides a remarkable opportunity for Windows developers to create state-of-the-art mobile applications using their existing skills and a familiar toolset. For iOS and Android developers, this book provides the right level of content to help developers rapidly come up to speed on Windows Phone. Pro Windows Phone 7 Development will help you unlock the potential of this platform and create dazzling, visually rich, and highly functional applications for the Windows Phone Marketplace. For developers new to the Windows Phone 7 platform, whether .NET, iPhone, or Android developers, this book starts by introducing you to the features and specifications of the Windows Phone series, and then leads you through the complete application development process. You'll learn how to use Microsoft technologies like Silverlight, .NET, the XNA Framework, Visual Studio, and Expression Blend effectively, how to take advantage of the available sensors such as the location service, accelerometer, and touch, make your apps location-aware using GPS data, utilize the rich media capabilities of the Windows Phone series, and much more. Finally, you'll receive a full tutorial on how to publish and sell your application through the Windows Phone Marketplace.